Treatment method for dealumination / aluminum supplementation of solid acid catalyst and application of treatment method

By using solid acid catalysts to continuously prepare 1,4-dioxane on a fixed bed reaction device, the problems of low raw material utilization and unstable preparation process in the traditional method are solved, and high selectivity and stable product preparation is achieved, with the advantages of environmental protection and easy separation.

CN119633886APending Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411632649.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The traditional 1,4-dioxane preparation method has problems such as low utilization rate of raw materials, unstable preparation process, difficulty in purifying and separation of products, waste acid production, corrosiveness to the equipment and serious pollution.

Method used

1,4-dioxane was prepared by continuous method on a fixed bed reaction device by using solid acid catalyst. By using diethylene glycol/ethylene glycol as raw material, the reaction was carried out under the action of a multi-stage porous solid acid catalyst to obtain a highly selective and stable product.

Benefits of technology

The continuous and highly selective preparation of 1,4-dioxane is achieved, which improves the quality and stability of the product, reduces the use of inorganic acid catalysts, is easy to separate, and is of environmental significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136358160000131
    Figure BDA0005136358160000131
  • Figure BDA0005136358160000141
    Figure BDA0005136358160000141
Patent Text Reader

Abstract

The invention discloses a treatment method for dealumination / aluminum supplementation of a solid acid catalyst and application, and the treatment method at least comprises the following steps: I, adding a guiding agent solution into acidic molecular sieve raw powder, and adding an aluminum supplementation substance to form slurry I; iI, transferring the slurry I obtained in the step I into a hydrothermal kettle, crystallizing and roasting I to obtain pretreated powder; and step III, adding an ammonium salt solution into the pretreated powder obtained in the step II to form slurry II, carrying out water bath ion exchange, and roasting II to obtain the hierarchical pore solid acid catalyst. According to the invention, the use of a liquid acid catalyst can be reduced, and the used catalyst is environment-friendly, high in conversion rate and high in selectivity and has environmental protection significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a solid acid catalyst dealumination / aluminization treatment method and application thereof, belonging to the field of chemistry and chemical engineering. Background Art

[0002] 1,4-Dioxane is a six-membered ring structure containing two ether bonds. It is an important chemical with stable structural properties and is widely used in the fields of medicine, cosmetics, fragrances, etc. In addition, it is miscible with most organic matter and water and is an excellent solvent. It has good solubility in cellulose acetate, resin, vegetable oil, mineral oil, oil-soluble fuel, etc. It is also used in the preparation of spray paint, varnish, plasticizer, wetting agent, and as a high-purity metal surface treatment agent.

[0003] U.S. Patent No. 1,681,861 discloses a method for preparing 1,4-dioxane, wherein diethylene glycol is used as a raw material and concentrated sulfuric acid is used as a dehydration catalyst to obtain 1,4-dioxane.

[0004] Chinese patent CN87102847A discloses a method for synthesizing 1,4-dioxane, which uses diethylene glycol as a raw material and concentrated sulfuric acid as a catalyst to synthesize 1,4-dioxane under negative pressure.

[0005] Feng Wenguo et al. published in “Synthesis of 1,4-dioxane by Catalysis of High-Temperature Resistant Resin Fixed Bed” (Petrochemical Industry, 1999, 28(3), 175) that 1,4-dioxane was prepared using diethylene glycol as raw material and self-made high-temperature resistant macroporous cation exchange resin as catalyst. The study showed that the conversion rate and selectivity of the reaction reached 93.7% and 90.4% respectively, showing a good reaction effect.

[0006] The traditional preparation method of 1,4-dioxane mainly adopts the intermittent method, in which diethylene glycol is dehydrated to generate 1,4-dioxane under the catalytic action of sulfuric acid. The main problems of this method are low raw material utilization, unstable preparation process, difficult product purification and separation, waste acid generation, corrosion to equipment, and serious pollution. Therefore, the development of a continuous method for preparing 1,4-dioxane will have a broader application prospect. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing 1,4-dioxane in a continuous manner. Using diethylene glycol / ethylene glycol as raw materials and a solid acid catalyst, 1,4-dioxane is prepared continuously and highly selectively in a fixed bed reaction device.

[0008] According to one aspect of the present application, a method for dealing with aluminization / aluminization of a solid acid catalyst is provided, comprising at least the following steps:

[0009] Step I: adding the directing agent solution to the acidic molecular sieve raw powder and adding aluminum supplementing material to form slurry I;

[0010] Step II: transferring the slurry I obtained in step I to a hydrothermal reactor, crystallizing and calcining I to obtain a pretreated powder;

[0011] Step III: adding the ammonium salt solution to the pretreated powder obtained in step II to form slurry II, and conducting ion exchange and calcining II in a water bath to obtain a hierarchical porous solid acid catalyst.

[0012] Optionally, the directing agent in the directing agent solution is selected from at least one of n-butylamine, ethylenediamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, ammonia water, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, ammonium fluoride, ammonium chloride, ammonium sulfate and ammonium nitrate.

[0013] Optionally, the liquid-to-solid ratio of the slurry I is 10 to 50 mL·g -1 ;

[0014] The molecular sieve in the acidic molecular sieve raw powder is at least one selected from hydrogen-type Beta molecular sieve, hydrogen-type mordenite molecular sieve, hydrogen-type ferrierite molecular sieve, hydrogen-type MCM-22 molecular sieve, hydrogen-type Y zeolite molecular sieve, hydrogen-type ZSM-5 molecular sieve, hydrogen-type ZSM-11 molecular sieve, hydrogen-type ZSM-22 molecular sieve, and hydrogen-type ZSM-23 molecular sieve.

[0015] Optionally, the aluminum supplement substance is selected from at least one of aluminum sulfate, aluminum nitrate, sodium aluminate, aluminum acetate, and aluminum isopropoxide.

[0016] Optionally, the silicon-aluminum ratio of the dealumination / aluminization is (20-200):1.

[0017] Optionally, the crystallization conditions are as follows:

[0018] The crystallization temperature is 120-200°C;

[0019] The crystallization time is 20 to 120 hours.

[0020] Optionally, the conditions of the roasting I are as follows:

[0021] The temperature of the calcination I is 350-750° C.;

[0022] The calcination time is 2 to 10 hours.

[0023] Optionally, the ammonium salt is selected from at least one of ammonium sulfate, ammonium nitrate, ammonium chloride and ammonium fluoride.

[0024] Optionally, the concentration of the ammonium salt solution is 0.1-2 mol / L.

[0025] Optionally, the liquid-to-solid ratio of the slurry II is 5 to 50 mL·g -1 .

[0026] Optionally, the conditions of the water bath ion exchange are as follows:

[0027] The temperature of the water bath ion exchange is 40 to 90°C;

[0028] The time of the water bath ion exchange is 4 to 24 hours.

[0029] Optionally, the water bath ion exchange is performed 1 to 5 times.

[0030] Optionally, the conditions of the calcination II are as follows:

[0031] The temperature of the calcination II is 350-750°C;

[0032] The calcination time of II is 2 to 10 hours.

[0033] According to another aspect of the present application, a method for dealumination / aluminization of a solid acid catalyst is provided for use in the continuous preparation of 1,4-dioxane, wherein diethylene glycol / ethylene glycol is used as a raw material and reacted in a fixed bed reactor under the action of a multi-stage porous solid acid catalyst to obtain a product containing 1,4-dioxane.

[0034] Optionally, the mass concentration of diethylene glycol / ethylene glycol is 10% to 100%.

[0035] Optionally, the structure type of the catalyst in the multi-level porous solid acid catalyst is selected from at least one of BEA, MOR, FER, MWW, FAU, and MFI.

[0036] Optionally, the reaction conditions are as follows:

[0037] The reaction temperature is 100-300°C;

[0038] The reaction pressure is 0.1-8 MPa;

[0039] The liquid mass space velocity of the raw material is 0.5 to 10 h -1 .

[0040] As a specific implementation method, the present invention uses diethylene glycol / ethylene glycol as a raw material and a solid acid catalyst to continuously and highly selectively prepare 1,4-dioxane in a fixed bed reaction device. In order to achieve the above purpose, the present invention adopts the following technical solution:

[0041] (1) Adding diethylene glycol / ethylene glycol solution into the raw material tank, the mass concentration of which is 10%-100%;

[0042] (2) Use a plunger pump to pump the raw materials into a fixed bed reactor filled with a solid acid catalyst for reaction at a reaction temperature of 100-300°C, a reaction pressure of 0.1-8MPa, and a liquid space velocity of 0.5-10h -1 ;

[0043] The structural type of the solid acid catalyst in the present application is selected from at least one of BEA, MOR, FER, MWW, FAU, and MFI;

[0044] The acidic molecular sieve catalyst is at least one selected from hydrogen-type Beta molecular sieve, hydrogen-type mordenite molecular sieve, hydrogen-type ferrierite molecular sieve, hydrogen-type MCM-22 molecular sieve, hydrogen-type Y zeolite molecular sieve, hydrogen-type ZSM-5 molecular sieve, hydrogen-type ZSM-11 molecular sieve, hydrogen-type ZSM-22 molecular sieve, and hydrogen-type ZSM-23 molecular sieve.

[0045] In the present application, the solid acid catalyst is subjected to desiliconization / aluminization treatment, and the process is as follows:

[0046] (1) Add the directing agent solution to the acidic molecular sieve powder at a liquid-solid ratio of 10-50 mL·g-1, and add the aluminum supplement to the above solution at a certain silicon-aluminum ratio, and stir it thoroughly on a magnetic stirrer. (2) Crystallize in a hydrothermal kettle. After the crystallization is completed, wash to neutrality, dry overnight, and roast.

[0047] (3) A 1.0 M NH4NO3 solution was added to the solid powder at a liquid-solid ratio of 20 mL·g-1, and ion exchange was performed three times in a water bath at 80°C. After overnight drying and calcination, a hierarchical porous solid acid catalyst was obtained.

[0048] The directing agent described in the present application is at least one of n-butylamine, ethylenediamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, ammonia water, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, ammonium fluoride, ammonium chloride, ammonium sulfate, and ammonium nitrate.

[0049] The silicon-aluminum ratio of desiliconization / aluminum supplementation described in this application is (20-200): 1

[0050] The crystallization temperature of desiliconization / aluminum supplementation described in the present application is 120-200°C.

[0051] The desiliconization / aluminum supplementation crystallization time described in this application is 20-120h.

[0052] The aluminum supplement material described in the present application is one or more of aluminum sulfate, aluminum nitrate, sodium aluminate, aluminum acetate, and aluminum isopropoxide.

[0053] The 1.0M NH4 +The solution is one or more of ammonium sulfate, ammonium nitrate, ammonium chloride and ammonium fluoride.

[0054] Other components in the diethylene glycol / ethylene glycol solution described in the present application are one or more of water, tetrahydrofuran, cyclohexane, acetonitrile, acetone, toluene, xylene, and methanol.

[0055] The beneficial effects of this application include:

[0056] 1) The application provided in this application can continuously produce 1,4-dioxane using a fixed bed reaction device, thereby improving the quality and stability of the product.

[0057] 2) The multiphase solid acid catalyst obtained by the treatment method provided in the present application can reduce the use of inorganic acid catalysts, is easy to separate, and is more environmentally friendly. DETAILED DESCRIPTION

[0058] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0059] Unless otherwise specified, the raw materials and reagents in the examples of this application were purchased through commercial channels.

[0060] The analysis methods in the examples and comparative examples of the present application are as follows:

[0061] Gas chromatography is used to analyze the components in the system, and quantification is performed through calibration and normalization, which can be carried out in accordance with existing technologies, and on this basis, evaluation indicators such as the conversion rate of the reactants and the selectivity of the products are calculated.

[0062] Conversion rate of diethylene glycol = ((carbon moles of diethylene glycol in feed) - (carbon moles of diethylene glycol in output)) / (carbon moles of diethylene glycol in feed) * 100%;

[0063] Selectivity of 1,4-dioxane=(the molar number of carbon atoms of diethylene glycol ether in the output) / ((the molar number of carbon atoms of diethylene glycol in the feed)-(the molar number of carbon atoms of diethylene glycol in the output))*100%.

[0064] The conversion rate of ethylene glycol is calculated in the same way as above.

[0065] Comparative Example 1

[0066] 20g of hydrogen-type mordenite molecular sieve catalyst with a silicon-aluminum ratio of 25 was calcined at 550℃ in a muffle furnace under air atmosphere for 6h, and then taken out and tableted, crushed, and sieved into 20-40m for testing. 5g of the catalyst sample was weighed and loaded into a stainless steel reactor with an inner diameter of 10.0mm. The reaction temperature was 180℃, and the etherification reaction raw materials diethylene glycol / water = 80 / 20 (mass ratio) were introduced, and the pressure was slowly increased to a reaction pressure of 2.0MPa. The mass space velocity of the reaction raw materials was 2.0h -1 The product was analyzed by gas chromatography. After the reaction stabilized, the conversion rate of diethylene glycol and the selectivity of the product 1,4-dioxane were calculated. The reaction results are shown in Table 1.

[0067] Example 1

[0068] 20 g of hydrogen-type mordenite molecular sieve catalyst with a silicon-aluminum ratio of 25 was calcined at 550°C for 6 h in a muffle furnace under air atmosphere; (1) 200 mL of 0.2 M tetramethylammonium hydroxide aqueous solution was added to 10 g of acidic molecular sieve mordenite raw powder, and 0.82 g of sodium aluminate was added to the above solution, and stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1 slurry; (2) the slurry formed in step (1) was transferred to a hydrothermal reactor and crystallized at 170°C for 48 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a solid powder; (3) 200 mL of 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form a liquid-to-solid ratio of 20 mL·g -1 The slurry is ion exchanged three times in a water bath at 80° C.; dried overnight, and calcined at 550° C. for 6 h to obtain a hierarchical porous solid acid catalyst.

[0069] The remaining experimental steps and reaction conditions were consistent with those of Comparative Example 1. The reaction results are shown in Table 1.

[0070] Example 2

[0071] 20 g of hydrogen-type mordenite molecular sieve catalyst with a silicon-aluminum ratio of 25 was calcined at 550°C for 6 h in a muffle furnace under air atmosphere; (1) 200 mL of 0.2 M tetrapropylammonium hydroxide aqueous solution was added to 10 g of acidic mordenite molecular sieve raw powder to form a liquid-to-solid ratio of 20 mL g -1 slurry; fully stirred on a magnetic stirrer for 2 hours; (2) the slurry formed in step (1) was transferred to a hydrothermal kettle and crystallized at 170°C for 48 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a multi-level porous solid acid catalyst.

[0072] The remaining experimental steps and reaction conditions were consistent with those of Comparative Example 1. The reaction results are shown in Table 1.

[0073] Example 3

[0074] 20 g of hydrogen-type mordenite molecular sieve catalyst with a silicon-aluminum ratio of 25 was calcined at 550° C. for 6 h in a muffle furnace under air atmosphere; (1) 100 mL of 0.2 M tetrapropylammonium hydroxide and 100 mL of 0.2 M ammonia aqueous solution were added to 10 g of acidic mordenite molecular sieve raw powder, and 0.82 g of sodium aluminate was added to the above solution; the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1 slurry; (2) the slurry formed in step (1) was transferred to a hydrothermal reactor and crystallized at 170°C for 72 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a solid powder; (3) 200 mL of 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form 20 mL·g -1 The slurry has a liquid-to-solid ratio, and the slurry is ion exchanged three times in a water bath at 80° C.; it is dried overnight and calcined at 550° C. for 6 hours to obtain a hierarchical porous solid acid catalyst.

[0075] The remaining experimental steps and reaction conditions were consistent with those of Comparative Example 1. The reaction results are shown in Table 1.

[0076] Comparative Example 2

[0077] 20g of hydrogen-type Beta zeolite molecular sieve catalyst with a silicon-aluminum ratio of 68 was calcined at 550℃ in a muffle furnace under air atmosphere for 6h, and then tableted, crushed, and sieved into 20-40m for testing. 5g of the catalyst sample was weighed and loaded into a stainless steel reactor with an inner diameter of 10.0mm. The reaction temperature was 180℃, and the etherification reaction raw materials diethylene glycol / tetrahydrofuran = 60 / 40 (mass ratio) were introduced, and the pressure was slowly increased to a reaction pressure of 3.0MPa. The mass space velocity of the reaction raw materials was 3.0h -1 The product was analyzed by gas chromatography. After the reaction stabilized, the conversion rate of diethylene glycol and the selectivity of the product 1,4-dioxane were calculated. The reaction results are shown in Table 1.

[0078] Example 4

[0079] 20 g of hydrogen-type Beta zeolite molecular sieve catalyst with a silicon-aluminum ratio of 68 was calcined at 550° C. for 6 h in a muffle furnace under air atmosphere; (1) 200 mL of 0.2 M tetrapropylammonium hydroxide aqueous solution was added to 10 g of acidic Beta zeolite raw powder, and 0.82 g of sodium aluminate was added to the above solution, and the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1slurry; (2) the slurry formed in step (1) was transferred to a hydrothermal reactor and crystallized at 150°C for 72 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a solid powder; (3) 200 mL of a 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form a liquid-to-solid ratio of 20 mL·g -1 The slurry is ion exchanged three times in a water bath at 80° C.; dried overnight, and calcined at 550° C. for 6 h to obtain a hierarchical porous solid acid catalyst.

[0080] The remaining experimental steps and reaction conditions were consistent with those of Comparative Example 1. The reaction results are shown in Table 1.

[0081] Example 5

[0082] 20 g of hydrogen-type Beta zeolite molecular sieve catalyst with a silicon-aluminum ratio of 68 was calcined at 550° C. in an air atmosphere in a muffle furnace for 6 h; (1) 100 mL of a 0.2 M tetrapropylammonium hydroxide aqueous solution was added to 10 g of acidic Beta zeolite raw powder, and 0.82 g of sodium aluminate was added to the above solution, and then 100 mL of 0.4 M hexadecyltrimethylammonium bromide was added, and the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1 slurry; (2) the slurry formed in step (1) was transferred to a hydrothermal reactor and crystallized at 150°C for 72 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a solid powder; (3) 200 mL of a 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form a liquid-to-solid ratio of 20 mL·g -1 The slurry is ion exchanged three times in a water bath at 80° C.; dried overnight, and calcined at 550° C. for 6 h to obtain a hierarchical porous solid acid catalyst.

[0083] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 2. The reaction results are shown in Table 1.

[0084] Example 6

[0085] The reaction raw materials were ethylene glycol / tetrahydrofuran = 80 / 20 (mass ratio), and the remaining experimental steps and reaction conditions were consistent with Example 5. The reaction results are shown in Table 1.

[0086] Comparative Example 3

[0087] 20g of hydrogen-type MCM-22 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 40 was calcined at 550℃ in a muffle furnace under air atmosphere for 6h, and then tableted, crushed, and sieved into 20-40m for testing. 5g of the catalyst sample was weighed and loaded into a stainless steel reactor with an inner diameter of 10.0mm. The reaction temperature was 160℃, and the etherification reaction raw materials diethylene glycol / tetrahydrofuran = 50 / 50 (mass ratio) were introduced, and the pressure was slowly increased to a reaction pressure of 3.0MPa. The mass space velocity of the reaction raw materials was 3.0h -1 The product was analyzed by gas chromatography. After the reaction stabilized, the conversion rate of diethylene glycol and the selectivity of the product 1,4-dioxane were calculated. The reaction results are shown in Table 1.

[0088] Example 7

[0089] 20 g of hydrogen-type MCM-22 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 40 was calcined at 550°C for 6 h in a muffle furnace under air atmosphere; (1) 200 mL of 0.2 M tetraethylammonium hydroxide aqueous solution was added to 10 g of acidic molecular sieve MCM-22 zeolite raw powder; the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL·g -1 (2) transferring the slurry obtained in step (1) to a hydrothermal reactor and crystallizing at 170°C for 72 hours. After the crystallization, washing to neutrality, drying overnight, and calcining at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a hierarchical porous solid acid catalyst.

[0090] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 3. The reaction results are shown in Table 1.

[0091] Example 8

[0092] 20 g of hydrogen-type MCM-22 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 40 was calcined at 550° C. for 6 h in a muffle furnace under air atmosphere; (1) 100 mL of 0.2 M ammonia aqueous solution was added to 10 g of acidic molecular sieve MCM-22 zeolite raw powder, and 0.41 g of sodium aluminate was added to the above solution, and then 100 mL of 0.4 M hexadecyltrimethylammonium bromide was added, and the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1 slurry; (2) the slurry obtained in step (1) was transferred to a hydrothermal reactor and crystallized at 170°C for 72 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours; (3) 200 mL of 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form a liquid-to-solid ratio of 20 mL·g -1 The slurry is ion exchanged three times in a water bath at 80° C.; dried overnight, and calcined at 550° C. for 6 h to obtain a hierarchical porous solid acid catalyst.

[0093] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 3. The reaction results are shown in Table 1.

[0094] Example 9

[0095] 20 g of hydrogen-type MCM-22 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 40 was calcined at 550° C. in an air atmosphere in a muffle furnace for 6 h; (1) 50 mL of a 0.2 M tetraethylammonium hydroxide aqueous solution was added to 10 g of acidic molecular sieve MCM-22 zeolite raw powder, and 0.41 g of sodium aluminate was added to the above solution, and then 50 mL of 0.3 M hexadecyltrimethylammonium bromide was added, and the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 10 mL g -1 slurry; (2) the slurry obtained in step (1) was transferred to a hydrothermal reactor and crystallized at 170°C for 72 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a solid powder; (3) 200 mL of a 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form a liquid-to-solid ratio of 20 mL·g -1 The slurry is ion exchanged three times in a water bath at 80° C.; dried overnight, and calcined at 550° C. for 6 h to obtain a hierarchical porous solid acid catalyst.

[0096] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 3. The reaction results are shown in Table 1.

[0097] Example 10

[0098] 20 g of hydrogen-type MCM-22 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 40 was calcined at 550° C. in an air atmosphere in a muffle furnace for 6 h; (1) 50 mL of 0.3 M tetrapropylammonium hydroxide and 20 mL of 0.1 M ammonium aqueous solution were added to 10 g of acidic molecular sieve MCM-22 zeolite raw powder, and 0.41 g of sodium aluminate was added to the above solution, and then 30 mL of 0.2 M hexadecyltrimethylammonium bromide was added, and the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 10 mL g -1 slurry; (2) the slurry obtained in step (1) was transferred to a hydrothermal reactor and crystallized at 170°C for 72 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a solid powder; (3) 200 mL of 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form a liquid-to-solid ratio of 20 mL·g -1 The slurry is ion exchanged three times in a water bath at 80° C.; dried overnight, and calcined at 550° C. for 6 h to obtain a hierarchical porous solid acid catalyst.

[0099] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 3. The reaction results are shown in Table 1.

[0100] Comparative Example 4

[0101] 20g of hydrogen-type ZSM-35 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 60 was calcined at 550℃ in an air atmosphere in a muffle furnace for 6h, and then tableted, crushed, and sieved into 20-40m for testing. 5g of the catalyst sample was weighed and loaded into a stainless steel reactor with an inner diameter of 10.0mm. The reaction temperature was 190℃, and the etherification reaction raw materials diethylene glycol / acetonitrile = 40 / 60 (mass ratio) were introduced, and the pressure was slowly increased to a reaction pressure of 3.0MPa. The mass space velocity of the reaction raw materials was 3.0h -1 The product was analyzed by gas chromatography. After the reaction stabilized, the conversion rate of diethylene glycol and the selectivity of the product 1,4-dioxane were calculated. The reaction results are shown in Table 1.

[0102] Embodiment 11

[0103] 20 g of hydrogen-type ZSM-35 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 60 was calcined at 550°C for 6 h in a muffle furnace under air atmosphere; (1) 200 mL of 0.2 M tetrapropylammonium hydroxide aqueous solution was added to 10 g of acidic molecular sieve ZSM-35 zeolite raw powder and stirred for 2 h on a magnetic stirrer to form a liquid-to-solid ratio of 20 mL g -1 (2) transferring the slurry obtained in step (1) to a hydrothermal reactor and crystallizing at 170°C for 48 hours. After the crystallization, washing to neutrality, drying overnight, and calcining at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a hierarchical porous solid acid catalyst.

[0104] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 4. The reaction results are shown in Table 1.

[0105] Example 12

[0106] 20 g of hydrogen-type ZSM-35 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 60 was calcined at 550° C. for 6 h in an air atmosphere in a muffle furnace; (1) 100 mL of 0.2 M tetrapropylammonium hydroxide and 40 mL of 0.1 M ammonium aqueous solution were added to 10 g of acidic molecular sieve ZSM-35 zeolite raw powder, and 0.82 g of sodium aluminate was added to the above solution, and then 60 mL of 0.4 M hexadecyltrimethylammonium bromide was added, and the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1slurry; (2) the slurry obtained in step (1) was transferred to a hydrothermal reactor and crystallized at 170°C for 72 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a solid powder; (3) 200 mL of 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form a liquid-to-solid ratio of 20 mL·g -1 The slurry is ion exchanged three times in a water bath at 80° C.; dried overnight, and calcined at 550° C. for 6 h to obtain a hierarchical porous solid acid catalyst.

[0107] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 3. The reaction results are shown in Table 1.

[0108] Example 13

[0109] The reaction raw materials were ethylene glycol / toluene = 30 / 70 (mass ratio), and the remaining experimental steps and reaction conditions were consistent with Example 12. The reaction results are shown in Table 1.

[0110] Comparative Example 5

[0111] 20g of hydrogen-type ZSM-5 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 74 was calcined at 550℃ in a muffle furnace under air atmosphere for 6h, and then taken out and tableted, crushed, and sieved into 20-40m for testing. 5g of the catalyst sample was weighed and loaded into a stainless steel reactor with an inner diameter of 10.0mm. The reaction temperature was 170℃, and the etherification reaction raw materials diethylene glycol / tetrahydrofuran = 50 / 50 (mass ratio) were introduced, and the pressure was slowly increased to a reaction pressure of 3.0MPa. The mass space velocity of the reaction raw materials was 3.0h -1 The product was analyzed by gas chromatography. After the reaction stabilized, the conversion rate of diethylene glycol and the selectivity of the product 1,4-dioxane were calculated. The reaction results are shown in Table 1.

[0112] Embodiment 14

[0113] 20 g of hydrogen-type ZSM-5 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 74 was calcined at 550°C in an air atmosphere in a muffle furnace for 6 h; (1) 200 mL of a 0.2 M n-butylamine aqueous solution was added to 10 g of acidic molecular sieve ZSM-5 zeolite raw powder and stirred for 2 h on a magnetic stirrer to form a liquid-to-solid ratio of 20 mL g -1 (2) the slurry obtained in step (1) was transferred to a hydrothermal autoclave and crystallized at 150°C for 72h; after the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in an air atmosphere in a muffle furnace for 6h to obtain a multi-level porous solid acid catalyst.

[0114] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 5. The reaction results are shown in Table 1.

[0115] Embodiment 15

[0116] 20 g of hydrogen-type ZSM-5 zeolite molecular sieve catalyst with a silicon-aluminum ratio of 74 was calcined at 550° C. in an air atmosphere in a muffle furnace for 6 h; (1) 100 mL of a 0.2 M n-butylamine aqueous solution was added to 10 g of acidic molecular sieve ZSM-5 zeolite raw powder, and 0.82 g of sodium aluminate was added to the above solution, and then 100 mL of 0.4 M hexadecyltrimethylammonium chloride was added, and the mixture was stirred on a magnetic stirrer for 2 h, and stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1 slurry; (2) the slurry obtained in step (1) was transferred to a hydrothermal reactor and crystallized at 150°C for 72 hours. After the crystallization, it was washed to neutrality, dried overnight, and calcined at 550°C in a muffle furnace under air atmosphere for 6 hours to obtain a solid powder; (3) 200 mL of a 1.0 M NH4NO3 solution was added to the solid powder obtained in step (2) to form a liquid-to-solid ratio of 20 mL·g -1 The slurry is ion exchanged three times in a water bath at 80° C.; dried overnight, and calcined at 550° C. for 6 h to obtain a hierarchical porous solid acid catalyst.

[0117] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 5. The reaction results are shown in Table 1.

[0118] Example 16

[0119] The reaction raw materials were ethylene glycol / methanol = 50 / 50 (mass ratio), and the remaining experimental steps and reaction conditions were consistent with Example 15. The reaction results are shown in Table 1.

[0120] Comparative Example 6

[0121] 20g of hydrogen-type Y zeolite molecular sieve catalyst with a silicon-aluminum ratio of 7 was calcined at 550℃ in a muffle furnace under air atmosphere for 6h, and then taken out and tableted, crushed, and sieved into 20-40m for testing. 5g of the catalyst sample was weighed and loaded into a stainless steel reactor with an inner diameter of 10.0mm. The reaction temperature was 180℃, and the etherification reaction raw materials diethylene glycol / water = 50 / 50 (mass ratio) were introduced, and the pressure was slowly increased to a reaction pressure of 2.0MPa. The mass space velocity of the reaction raw materials was 3.0h -1 The product was analyzed by gas chromatography. After the reaction stabilized, the conversion rate of diethylene glycol and the selectivity of the product 1,4-dioxane were calculated. The reaction results are shown in Table 1.

[0122] Embodiment 17

[0123] 20 g of hydrogen-type Y zeolite molecular sieve catalyst with a silicon-aluminum ratio of 7 was calcined at 550°C in an air atmosphere in a muffle furnace for 6 h; (1) 200 mL of a 0.2 M n-butylamine aqueous solution was added to 10 g of acidic Y zeolite raw powder and stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1 (2) transferring the slurry obtained in step (1) to a hydrothermal reactor and crystallizing at 120° C. for 72 h. After the crystallization, washing to neutrality, drying overnight, and calcining at 550° C. for 6 h in a muffle furnace under air atmosphere to obtain a hierarchical porous solid acid catalyst.

[0124] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 6. The reaction results are shown in Table 1.

[0125] Embodiment 18

[0126] 20 g of hydrogen-type Y zeolite molecular sieve catalyst with a silicon-aluminum ratio of 7 was calcined at 550°C in an air atmosphere in a muffle furnace for 6 h; (1) 100 mL of 0.2 M ethylenediamine aqueous solution was added to 10 g of acidic Y zeolite raw powder, and then 100 mL of 0.4 M hexadecyltrimethylammonium chloride was added, and the mixture was stirred on a magnetic stirrer for 2 h to form a liquid-to-solid ratio of 20 mL g -1 (2) transferring the slurry obtained in step (1) to a hydrothermal reactor and crystallizing at 120° C. for 72 h. After the crystallization, washing to neutrality, drying overnight, and calcining at 550° C. for 6 h in a muffle furnace under air atmosphere to obtain a hierarchical porous solid acid catalyst.

[0127] The remaining experimental steps and reaction conditions are consistent with those of Comparative Example 6. The reaction results are shown in Table 1.

[0128] Table 1

[0129]

[0130]

[0131] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for dealumination / aluminization of a solid acid catalyst, characterized in that: At least the following steps are included: Step I: adding the directing agent solution to the acidic molecular sieve raw powder and adding aluminum supplementing material to form slurry I; Step II: transferring the slurry I obtained in step I to a hydrothermal reactor, crystallizing and calcining I to obtain a pretreated powder; Step III: adding the ammonium salt solution to the pretreated powder obtained in step II to form slurry II, and conducting ion exchange and calcining II in a water bath to obtain a hierarchical porous solid acid catalyst.

2. The processing method according to claim 1, characterized in that: The guiding agent in the guiding agent solution is selected from at least one of n-butylamine, ethylenediamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, ammonia water, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, ammonium fluoride, ammonium chloride, ammonium sulfate and ammonium nitrate; Preferably, the liquid-to-solid ratio of the slurry I is 10 to 50 mL·g -1 ; The molecular sieve in the acidic molecular sieve raw powder is at least one selected from hydrogen-type Beta molecular sieve, hydrogen-type mordenite molecular sieve, hydrogen-type ferrierite molecular sieve, hydrogen-type MCM-22 molecular sieve, hydrogen-type Y zeolite molecular sieve, hydrogen-type ZSM-5 molecular sieve, hydrogen-type ZSM-11 molecular sieve, hydrogen-type ZSM-22 molecular sieve, and hydrogen-type ZSM-23 molecular sieve.

3. The preparation method according to claim 1, characterized in that: The aluminum supplement material is selected from at least one of aluminum sulfate, aluminum nitrate, sodium aluminate, aluminum acetate, and aluminum isopropoxide; Preferably, the silicon-to-aluminum ratio of the desiliconization / aluminum supplementation is (20-200):

1.

4. The processing method according to claim 1, characterized in that: The crystallization conditions are as follows: The crystallization temperature is 120-200°C; The crystallization time is 20 to 120 hours; Preferably, the conditions of the calcination I are as follows: The temperature of the calcination I is 350-750° C.; The calcination time is 2 to 10 hours.

5. The processing method according to claim 1, characterized in that: The ammonium salt is selected from at least one of ammonium sulfate, ammonium nitrate, ammonium chloride and ammonium fluoride; Preferably, the concentration of the ammonium salt solution is 0.1 to 2.0 mol / L; Preferably, the liquid-to-solid ratio of the slurry II is 5 to 50 mL·g -1 .

6. The processing method according to claim 1, characterized in that: The conditions of the water bath ion exchange are as follows: The temperature of the water bath ion exchange is 40 to 90°C; The water bath ion exchange time is 4 to 24 hours; Preferably, the water bath ion exchange is performed 1 to 5 times; Preferably, the conditions of the calcination II are as follows: The temperature of the calcination II is 350-750°C; The calcination time of II is 2 to 10 hours.

7. Application of a solid acid catalyst dealumination / aluminization treatment method in the continuous preparation of 1,4-dioxane, characterized in that: Using diethylene glycol / ethylene glycol as raw materials, reacting in a fixed bed reactor under the action of a multi-stage porous solid acid catalyst to obtain a product containing 1,4-dioxane; The multi-level porous solid acid catalyst is obtained by any one of the treatment methods of claims 1 to 6.

8. The use according to claim 7, characterized in that: The mass concentration of the diethylene glycol / ethylene glycol is 10% to 100%.

9. The use according to claim 7, characterized in that: The structure type of the catalyst in the multi-level porous solid acid catalyst is selected from at least one of BEA, MOR, FER, MWW, FAU, and MFI.

10. The use according to claim 7, characterized in that: The reaction conditions are as follows: The reaction temperature is 100-300°C; The reaction pressure is 0.1-8 MPa; The liquid mass space velocity of the raw material is 0.5 to 10 h -1 .

Citation Information

Patent Citations

  • Synthesis of 1,4-dioxyhexacyclic compound

    CN87102847A

  • Process of a manufacture of dioxan

    US1681861A